Is Economics in Violation of International Law? Remaking Economics as a Social Science: Parts I-IV - Lempert, David (2018)
This piece is in four parts following this abstract, the Table of Contents and a Short Introduction. Part I: Is Economics in Violation of International Law? Part I applies a set of systematic international legal principles found in international law to the doctrines of “neo-classical” mainstream economics to test whether the discipline is consistent with those legal principles or would be held to be in violation if brought to trial in an international court of law. The conclusion of this legal analysis is that the discipline is in violation. Part II: Is there a Current Social Science of Economics in Economics or Elsewhere that Meets the Requirements of Social Science? If Not, Why Not? Part II then holds the discipline of economics to scrutiny as to whether it meets the test of being a “social science” and also applies a similar test to the sub-discipline of “economic anthropology” that has been a response to the ideologies in the discipline of economics. Although both claim to be social sciences, the conclusion is that both have largely become ideological rather than scientific, serving to promote political views (in the case of neo-classical economics, a technical field of national production engineering combined with an ideology to promote it). Part III: The Rebuilding Process for the Discipline: Where Economics Fits and What is Missing. Part III goes back to the goals of the social sciences and humanities in terms of their areas of analysis and questions for individual disciplines and then offers a new framework for a scientific discipline of economics and a new humanities of economics linked with it. This new economics as an empirical social science for prediction links measures of consumption, production and distribution to biological and ecological principles and replaces the current starting assumptions that are culturally biased “moral precepts.” It moves the discipline forward, beyond its position within industrial market systems where it serves as an ideological and technical tool to promote economic interests of elites in those systems. Part IV: The Challenge of Institutional and Cultural Change in Academia. The piece ends with a discussion pointing to the areas of society that would need to change in order for a scientific and international law compliant discipline to emerge